An Empirical View of Business Ethics on Press Freedom: A Case Study - Diyana, Kamarudin; Faiz, Azizul; Wan Khairul Anuar, Wan Abd Manan (KnE Social Sciences, 2019)
Press freedom in Malaysia is bound under several regulations and restrictions ever since Malaysia granted independence in 1957. Due to this, a few media and press laws were also inadvertently inherited from the draconian colonial law or introduced in controlling any extremist actions during emergency periods and also used in silencing any political rivals. Based on the report compiled by Reporters without Borders (RSF), Malaysia jumped 22 places to 123rd of the World Press Freedom Index in 2019, better than all of our South East Asian neighboring countries. The success of Malaysia press freedom movement triggered by the reformation of a few media institutions, laws, and practices throughout the year. The enhancement of Malaysia press freedom assisted in the development of the country and led the nation in becoming more progressive and transparent alongside other developing nations worldwide. In this research, a case study conducted at one of a privately-owned media organization headquarters in Kuala Lumpur, Malaysia is aimed to analyze the ethical issues regarding business ethics involving informal interviewing methods performed towards internal staff. The case recorded will then be categorized into four different setups. Each case from each category analyzed will discuss, in detail, the business ethic concept and ethical principles. In this study, the discussion aims to strengthen moral values and business ethics that has supposedly implemented in the media industry sector in Malaysia.